The Correlation of Quality of Life With Social Support for Kidney Transplant Patients - Afsar Omidi; hussin gholinezhad; Massoud Khodawasi; Ghodratollah roshanaei (Hamadan University of Medical Sciences, 2018)
Introduction: Kidney transplantation is the best treatment in end stage renal failure. Quality of life is an important factor in the survival of kidney transplants and these patients need social support to improve their quality of life. Therefore, the present study was conducted to determine the correlation between quality of life and social support in patients with renal transplantation. Methods: This descriptive cross-sectional study was a correlation study performed on 166 patients with kidney transplantation referred to the renal transplantation clinic of Shahid Beheshti Medical Center in Hamadan in the winter of 2016. Convenient sampling method  was used. Before the completion of the questionnaires, an informed consent was obtained and researcher was available during completion of questioners. Data was collected using demographic characteristics, Lapazis Quality of Life (KTQ-25) and Social Wax Support questionnaires. Data was analyzed by SPSS24 using Kolmogorov-Smirnov, Mann-Whitney, Kruskal-Wallis and Spearman non-parametric tests. Results: The mean score of total quality of life was 2.79 ± 0.99. The mean score of quality of life in the area of physical symptoms was higher than other areas (3.67) and the total score of social support was 69.91 ± 7.58. 80.7% of patients had an average quality of life. the mean score of social support in the family was more than other areas (25.61%). 57.2% of patients had a good level of social support. Social support had a direct and significant association with quality of life of patients (r = 0.371, P <0.05).  Conclusion: There was a direct and significant association between quality of life and the level of social support in patients with renal transplantation . Therefore, it is necessary to pay special attention to the role of families in increasing the quality of life of patients and consequently, their health promotion. Health care personnel can consider the quality and quantity of support needs of patients by mobilizing support resources in the community and family participation to improve the quality of life of patients and as a low-cost and effective way to improve their quality of life.